Expression of PD-L1/PD-1 in lymphoepithelioma-like carcinoma of the thymus. (December 2018) - Suster, David; Pihan, German; Mackinnon, Alexander C.; Suster, Saul
Abstract Poorly differentiated non-keratinizing squamous cell carcinoma of the thymus, also known as lymphoepithelioma-like carcinoma, is a rare primary malignant neoplasm of thymic origin. The mainstay of treatment for these tumors is surgical and they tend to respond poorly to chemotherapy. The checkpoint programmed cell death ligand-1 protein (PD-L1) bound to its receptor (PD-1) has been demonstrated to be an important therapeutic target for many different tumors. Expression of PD-L1/PD-1 in lymphoepithelioma-like carcinoma of the thymus may indicate that these tumors are potential targets for inhibitor therapy. Twenty-one cases of lymphoepithelioma-like carcinoma of the thymus were collected and reviewed. Tissue microarrays were created using triplicate 2 mm cores for each case. PD-L1/PD-1 staining pattern (neoplastic cells versus tumor infiltrating lymphocytes) was documented for each case. Out of 21 cases, 15 (71.4%) showed various degrees of membranous PD-L1 staining. Of the positive cases, 48% showed high expression of PD-L1 (>50% of tumor cells) and 24% showed low expression (<50%). PD-1 staining showed focal positivity in 12/20 (60%) cases among tumor infiltrating lymphocytes. PD-L1/PD-1 inhibitor therapy has been applied successfully in other solid malignant tumors with high expression of PD-L1/PD-1. The high level of PD-L1 expression in our cases indicates that PD-L1 may play a role in the pathogenesis of these tumors and that PD-L1/PD-1 blockade may be a viable therapeutic option for patients with lymphoepithelioma-like carcinoma of the thymus who have failed other first-line therapies.